THE PSYCHOLOGICAL BASIS OF BIRR AL-WALIDAYN: A Thematic Analysis of Quranic Verse 14–15 In Surah Luqman - Nabilah, Fadwa; Azizah, Alfiyatul (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
The Hadith about Jahimah, who sought the Prophet Muhammad’s permission to participate in battle but was instructed instead to stay with his mother because “Paradise lies beneath her feet,” underscores the noble value of devotion to one’s mother. This virtue is also reflected in Surah Luqman (31:14–15), where God describes the mother’s struggle during pregnancy and weaning as wahnun ‘alā wahnin (“weakness upon weakness”) and commands children to show gratitude to their parents. This study aims to examine the psychological foundation of the Qur’anic injunction of birrul wâlidain (devotion to parents) in Surah Luqman 31:14–15 through the perspectives of maternal psychology and humanistic psychology. Employing a library research method and a descriptive-analytical approach, the study explores two main aspects: first, the maternal psychological perspective, which highlights the emotional and physical challenges experienced by mothers during pregnancy, childbirth, and breastfeeding as formative factors in developing empathy and moral awareness in children; and second, the humanistic perspective, which emphasizes consciousness, empathy, and unconditional love as the essence of filial devotion. The findings reveal that the Qur’anic command to honor one’s parents—particularly the mother—constitutes not only a moral obligation but also an acknowledgment of maternal psychological resilience as the foundation for a harmonious parent–child relationship. Consequently, the moral message of Surah Luqman 31:14–15 transcends ethical instruction, reflecting an emotional and spiritual reciprocity between mother and child and reaffirming the relevance of birrul wâlidain in fostering familial affection and the cultivation of virtuous character.